Análise comparativa de modalidades contratuais e de métodos de gestão em obras de pequeno porte - Tamiris Ribeiro Narciso (2023)
The civil construction sector is a significant driver of the country's economy, with inherent socio-political representation and which directly impacts the national Gross Domestic Product (GDP). The sector is very heterogeneous and dynamic, which makes the stages of contracting and managing be complex jobs that require knowledge and control of the steps and processes of the project, to provide gains in productivity and business profitability. The typology and size of works in the civil construction sector are very diverse and, therefore, the contracting and management practices used in large constructions are not always suitable for smaller constructions, due to different dynamics, activity flows, construction site, among other factors. This research aimed to evaluate the contractual arrangements and the main limitations and contingencies faced in small constructions for commercial retail purposes, based on the analysis of their performance indicators. For this, a case study of 27 constructions of bank branches of a large financial institution in the country was carried out. The main problems and contingencies faced during the execution phase of these undertakings were mapped and quantified, and their time and cost performance indicators were calculated. At the same time, an electronic message was released which was answered by 24 construction companies that operate in the retail commercial constructions segment, where their occurrences were collected on the main failures faced and on the usual contractual modalities employed in these projects. The results were evaluated and confronted with the contractual modalities applied in each project. The research allows us to conclude that problems related to conception flaws (needs program) and project failures are the most recurrent in small commercial constructions and indicate that contractual modalities that promote greater integration between the agents involved in the design and construction processes, can provide better results within the dynamic and changing context of these constructions.